Using learning games for fourth-grade students to teach Vietnamese lessons and teachers’ perspectives on learning games - Le, Lan-Anh Thi; Tran, Quynh-Nga Thi; Nguyen, Kim-Dung Thi; Xuan, Ha Thi Nguyet (Journal of Education and e-Learning Research, 2023)
Students can learn in a meaningful way through the use of educational games. When students apply their skills and information in order to progress through a game, a huge degree of engagement is generated among them in the classroom as a result both their capabilities and their learning increase. 153 children from primary schools in Vietnam participated in this research. The children were split into two groups: an experimental and a control group. Both groups participated in two sessions of word and sentence practice as well as spelling instruction. According to the findings of the study, the educational outcomes of the students are greatly improved when games are used in their classrooms. In addition, research has shown that some teachers are against the use of games in the classroom since it makes it more difficult to prepare educational materials. Some educators believe that playing educational games is a more effective method of instruction as it allows for greater flexibility during the learning process. This makes a contribution to the theoretical framework that is necessary to guide educators and instructors in the process of improving learning game programs for children in primary schools and other learners.